Recent Advances in Histopathological and Molecular Diagnosis in Pheochromocytoma and Paraganglioma: Challenges for Predicting Metastasis in Individual Patients - Yamazaki, Yuto; Gao, Xin; Pecori, Alessio; Nakamura, Yasuhiro; Tezuka, Yuta; Omata, Kei; Ono, Yoshikiyo; Morimoto, Ryo; Satoh, Fumitoshi; Sasano, Hironobu (Frontiers in Endocrinology, 2020)
Pheochromocytomas and paragangliomas (PHEO/PGL) are rare but occasionally life-threatening neoplasms and all could potentially harbor malignant behavior or metastatic according to WHO classification in 2017. However, it has also been well known that histopathological risk stratification to predict the clinical outcomes has not necessarily been established. The first histopathological diagnostic algorithm of PHEO, “PASS” was proposed in 2002 by Thompson et al. with GAPP subsequently in 2014. However, both have not been widely accepted as the gold standard. This is because histopathological features of PHEO/PGL could be extremely diverse and independent of their hormonal activities as well as their clinical behaviors. Recent development of wide scale genetic analysis using next generation sequencing has indeed revealed the molecular characteristics of pheochromocytomas and paragangliomas. More than 30-40% of PHEO/PGL have been recently reported to be associated with hereditary genetic abnormalities of more than 20 genes, including SDHXs, RET, VHL, NF1, TMEM127, MAX, and others. Those genetic alterations have been reported to be mainly involved in the pathogenesis of pseudohypoxia, Wnt signaling, Kinase status and others. In addition, recurrent somatic mutations have been also frequently detected and overlapped with the presence of those genetic alterations associated with hereditary diseases. In addition, therapeutic strategy specifically targeting those genetic abnormalities above has been proposed but practically not used at least at this juncture. Therefore, we here review recent advance of the studies including histopathological and molecular analyses in order to summarize potential therapeutic targets or prognostic factors of the patients with PHEO/PGL.